(untitled) (Communications in Computational Physics, 2020)
In this paper we present a software package based on modern information technologies that allows rapid analysis and visualization of the properties of complex plasmas. The properties of plasma are simulated by two means. First of all, we have applied the molecular dynamics simulation method which numerically solves the equations of motions for plasma particles. Secondly, we calculate microscopic properties of plasma by using the Boltzmann equation with additional relations, initial and boundary conditions.